Ultrahigh charge–discharge efficiency and high energy density of a high-temperature stable sandwich-structured polymer. Issue 3 (4th January 2022) - Chen, Hanxi; Pan, Zhongbin; Cheng, Yu; Ding, Xiangping; Liu, Jinjun; Chi, Qingguo; Yang, Minhao; Yu, Jinhong; Dang, Zhi-Min
Abstract : Sandwich-structured polymer nanocomposites exhibit remarkable capacitive energy storage performance, including high energy density, great charge–discharge efficiency and excellent dielectric stability at elevated temperatures. Abstract : A new generation of high-temperature dielectric materials toward capacitive energy storage is highly demanded, as power electronics are always exposed to elevated temperatures in high-power applications. Polymer dielectric materials, as ideal candidates for capacitors, suffer from deteriorated energy density because of their depressed dielectric constant and decreased breakdown strength at high temperatures, which become major barriers for their application in harsh environments. Here, sandwich-structured dielectric polymer nanocomposites with superior high-temperature capacitive performances are reported. Very different from the conventional single-layer designs, such sandwich-structured configurations can integrate the complementary properties of multiple spatially organized components in a synergistic manner, simultaneously raising the dielectric constant and breakdown strength, and subsequently greatly increasing the discharged energy density at elevated temperatures. Further analysis by simulation shows the evolution process of electrical tree channels in the experimental breakdown and dissipation of Joule heating. Consequently, the sandwich-structured polymer nanocomposites deliver an outstanding U d value of 4.14 J cm −3, with a η value of above 90% at 150 °C, outperforming the current high-temperature dielectric polymers and composites. This work provides a new design paradigm for high-temperature electrical energy storage applications.